CLINIC CHARACTERISTICS OF PATIENTS WITH ENDOMETRIOSIS-ASSOCIATED INFERTILITY - Khmil S. V.; Kulyk I. I. (Вісник проблем біології і медицини, 2020)
Despite the fact that a lot of time has passed since the first mention of endometriosis as a disease, the pathogenesis of this disease has not been fully studied, as well as there is no clear definition of why endometriosis provokes infertility. Therefore, the aim of our study was to analyze the clinical characteristics of patients with endometriosis-associated infertility (EAI) depending on the treatment of endometrioid cysts. The study analyzed the data of medical records of 114 women aged 21 to 40 years with endometriosis-associated infertility, who were treated at the medical center “Clinic of Professor S. Khmil”. The control group included 30 women with tubal – peritoneal factor infertility. Analysis of the results of the study shows no differences in age distribution among patients of different groups. During the analysis of data on the distribution of women with EAI by duration of infertility depending on its type, it was found that most often in the first 5 years of diagnosed infertility non-operated women with monolateral endometrioid cysts came to the reproductive clinic, while for 10 years almost all women sought medical help. A burdensome reproductive history occurred in all women with EAI. Among the clinical manifestations of pain in women with EAI, algomenorrhea and dyspareunia in women with monoor bilateral cysts on the previously operated ovary predominated. Urogenital infection was dominated in the structure of extragenital diseases in all experimental groups. Chronic salpingoophoritis prevailed in the structure of gynecological diseases in patients with EAI. When distributing patients with EAI depending on the number of cysts in the affected ovary, it was found that the largest number of women has one cyst. Thus, risk factors for endometriosis-associated infertility include hormonal dysbalance, inflammatory diseases of the female genital organs, the presence of a history of surgery, abortion, abnormal childbirth. The use of assisted reproductive technologies to treat endometriosis-associated infertility is equally needed in non-operated women and those with a history of surgical treatment of endometrioid cysts.